Effect of camel milk on glucose metabolism in adults with normal glucose tolerance and type 2 diabetes in Raica community: a crossover study - Agrawal, R.P.; Sharma, P.; Gafoorunissa, et al., S.J. (Acta Biomedica Atenei Parmensis, 2012)
Background: To investigate effects of camel milk consumption on insulin sensitivity and glycemic control in normal and type-2 diabetics of Raika and Non-Raika community. Methods: 28 raika and non-raika male were enrolled in study, categorized in 2 groups, non-diabetic and diabetic after one month stabilization. Non-diabetics were supplemented with cow milk and diabetics with camel milk; followed by one-month washout period. Afterwards regimen was interchanged for 3 months. Biochemical and anthropometric data was recorded at baseline, after stabilization, before and after washout and at end of study. Results: An improving trend was observed in both the groups for camel milk effect (FBS 203.86±24.09 to 161.43±11.39 mg/dl;p<0.05, OGTT 320.86±25.34 to 213.79±15.96 mg/dl;p<0.05 in diabetics and FBS 101.79±3.06 to 96.79±2.56 mg/dl, OGTT 114.36±7.99 to 100.36±6.74 mg/dl in control). HbA1c improved due to camel milk consumption (8.39±0.64 to 7.27±0.67%) whereas deteriorated in the case of cow milk (7.36±0.66 to 8.26±0.60%) in diabetic group. The HOMA-IR reduced from 13.21±4.88 to 4.38±0.75, AUC-glucose from 37253.57±2859.08 to 30724.29±3677.33 and AUC-insulin from 5871.86±1210.73 to 3301.86±629.98 in the camel milk group. Conclusions: In type-2 diabetics camel milk reduces FBS, post-prandial glucose and HbA1c. AUC-insulin and AUC-glucose also decreased significantly along with HOMA-IR. It shows hypoglycemic effect of camel milk reducing insulin resistance.